2020
DOI: 10.1111/tid.13397
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of the gut microbiome by immunosuppressive agents used in solid organ transplantation

Abstract: Introduction Studies have suggested that in addition to antimicrobials, some non‐antibiotics may alter the gut microbiome. This systematic review sought to determine if there is an association between immunosuppressive agents used in recipients of solid organ transplants (SOT) and alterations in the gut microbiome. Methods English language PubMed and Scopus searches were conducted to identify relevant articles. Inclusion criteria were defined as pertaining to solid organ transplantation, immunosuppression, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
(51 reference statements)
2
24
1
Order By: Relevance
“…MMF was able to prevent the development of hypertension in DOCA-salt due to pharmacological inhibition of B and T cell proliferation [17,18]. Recently, it has been described that MMF influences the gut microbiome in renal transplant patients [19][20][21][22] and rodents [23]. Renal transplant recipients suffer from dysbiosis, characterized by lower diversity and loss of butyrate-producing bacteria, more than one year post-transplantation, and the use of MMF correlates to a lower diversity [21].…”
Section: Introductionmentioning
confidence: 99%
“…MMF was able to prevent the development of hypertension in DOCA-salt due to pharmacological inhibition of B and T cell proliferation [17,18]. Recently, it has been described that MMF influences the gut microbiome in renal transplant patients [19][20][21][22] and rodents [23]. Renal transplant recipients suffer from dysbiosis, characterized by lower diversity and loss of butyrate-producing bacteria, more than one year post-transplantation, and the use of MMF correlates to a lower diversity [21].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, prednisolone in combination with mycophenolate and tacrolimus increased E. Coli colonization. Serial testing of fecal samples of kidney transplant recipients revealed that compared to those remaining on maintenance corticosteroid, patients with early GC withdrawal had numerically, but not statistically significant, lower Clostridiales and Erysipelotrichales [124] .…”
Section: Gastrointestinal Side Effectsmentioning
confidence: 88%
“…In that study, prednisolone, in combination with mycophenolate and tacrolimus, increased Escherichia coli colonization. Serial testing of fecal samples of kidney transplant recipients revealed that compared to those remaining on maintenance corticosteroid, patients with early GC withdrawal had numerically but not statistically significant lower Clostridiales and Erysipelotrichales [ 124 ].…”
Section: Side Effectsmentioning
confidence: 99%